The Influence of Brand Image on Brand Loyalty of Holywings Indonesia: The Role of Brand Trust to Building Consumer Engagement to Brands - Handayani, Yuliasti Ika; Erwita, Monica Adjeng (Ekonomi Bisnis, 2021)
Brands offer several benefits for consumers as well as for companies. A service brand not only indicates the quality of the service but also communicates a commitment to provide a certain type of experience. This study aims to explore the effect of brand image on brand loyalty, and how the role of brand trust in mediating these two variables. The research was conducted on visitors and connoisseurs of Holywings Indonesia bars and restaurants in Surabaya. The data were collected using a questionnaire as a research instrument, and the sample of this study was 100 respondents who live in Surabaya. The results of the study indicate that there is a significant positive relationship between brand image and brand trust, on brand loyalty of bars and restaurants Holywings Indonesia. Moreover, brand trust has a role as an intervening variable although the mediation model only shows a little contribution toward the context studied.